2001
DOI: 10.1348/000709901158532
|View full text |Cite
|
Sign up to set email alerts
|

Boys starting school disadvantaged: Implications from teachers’ ratings of behaviour and achievement in the first two years

Abstract: The outcomes of this study suggest that low SES boys commenced school significantly disadvantaged by a pattern of perceived distractible behaviour in particular, and that this perception continued to operate over the next two years of their schooling. Such a pattern implied that these boys were perceived by their teachers, from early in their school careers, as being demanding and difficult to teach. Once teachers gave certain boys a label it appeared to 'stick'. SES per se was thus not the main risk factor. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 16 publications
5
19
0
4
Order By: Relevance
“…Issues such as social context as an influence on masculine or feminine behavior (Frank et al 2003;Newman 2005), school and study culture (Van Houtte 2004), gender stereotypes in the classroom (Gray and Leith 2004), and single-gender classrooms (Mulholland et al 2004) were topics for discussion. Additionally, learning disabilities (Rutter et al 2004), impact of socioeconomic status (SES) on the gender gap (Childs and McKay 2001;Gorard et al 2001), and possible teacher/counsellor interventions Kniveton 1998;Moss 2000) were discussed in the classes as background information for the action research. Themes for interview and focus group questions were developed and shared by the university students via a WebCT format to which they all had access.…”
Section: Participantsmentioning
confidence: 99%
“…Issues such as social context as an influence on masculine or feminine behavior (Frank et al 2003;Newman 2005), school and study culture (Van Houtte 2004), gender stereotypes in the classroom (Gray and Leith 2004), and single-gender classrooms (Mulholland et al 2004) were topics for discussion. Additionally, learning disabilities (Rutter et al 2004), impact of socioeconomic status (SES) on the gender gap (Childs and McKay 2001;Gorard et al 2001), and possible teacher/counsellor interventions Kniveton 1998;Moss 2000) were discussed in the classes as background information for the action research. Themes for interview and focus group questions were developed and shared by the university students via a WebCT format to which they all had access.…”
Section: Participantsmentioning
confidence: 99%
“…In their study they found that teachers rated low SES females more favorably than high SES females while conversely rating low SES boys less favorably than high SES boys. These results mirrored similar studies (see Childs & McKay, 2001) suggesting that low-SES boys may be especially vulnerable to negative teacher expectations. Thus, since Brooklawn serves only boys and Maryhurst serves only girls, the results of Research Question I could be related to student gender; however it is difficult to ascertain this for certain.…”
Section: Discussion and Conclusion: Research Questionsupporting
confidence: 87%
“…The results of this study suggest that individual perceptions ofteacher efficacy trended downward with male students and upward with female students. This could be linked to prior studies demonstrating that teachers working with low SES populations tend to have negative expectations of their male students and positive expectations of their female students (Auwarter & Aruguete, 2008;Childs & McKay, 2001). As a result, teachers should be made aware of this tendency and encouraged to explore challenges unique to their respective institutions (e.g.…”
Section: Implications For Practicementioning
confidence: 88%
See 1 more Smart Citation
“…The study showed that teachers believe that students from poor economic backgrounds are unlikely to have the aptitude to succeed in their classes (Carter et al 2004). Childs and McKay (2001) examined teacher perceptions of learning behaviors among low and middleincome students. Teachers rated low SES boys as having poorer learning behaviors than middle SES boys and both low and middle SES girls.…”
mentioning
confidence: 99%